(untitled) (Research, Society and Development, 2021)
Objective: Evaluate the anti-biofilm activity of Gymnema sylvestre, Hamamelis virginiana, Juglans regia, Persea americana, Pfaffia paniculata, Rosmarinus officinalis, Stryphnodendron barbatiman and Thymus vulgaris extracts in 3 MDR strains and 1 ATCC (4352) of Klebsiella pneumoniae. Methods: First were made a screening with broth microdilution test, protocol M7-A9, according to CLSI. Extracts that presented values for Minimal Microbicidal Concentration (MMC) were selected for biofilms tests on 96 wells plates. Treatments used concentrations of 25 and 50 mg/mL, after biofilms were measured by biomass and MTT tests and statistically analyzed by ANOVA and Tukey test (p<0.05). Results: All extracts showed MIC for all K. pneumoniae strains studied, with values ranging from 12.5-100 mg/mL. Biomass of the strains ATCC and MDR strain (400381) of K. pneumoniae obtained reductions of 37.7 and 44.3% with P. paniculata and R. officinalis extracts. The isolate 386546 obtained a reduction of 29.7% (p<0.05) under R. officinalis action. Conclusion: Among the extracts studied, those that were most effective in the anti-biofilm action were J. regia, P. paniculata and R. officinalis. Therefore, these extracts could act as bactericidal agents against K. pneumoniae MDR.